CLINICAL VALUE OF MEASURMENT OF INTRA- ABDOMINAL PRESSURE AND ITS MONITORING IN EMERGENCY SURGERY - V. M. Timerbulatov; Sh. V. Timerbulatov; M. V. Timerbulatov; R. N. Gareev; R. A. Smyr (Вестник хирургии имени И.И. Грекова)
The article presents an analysis of modern methods of the measurement, including classical and original methods and devices developed by the authors. The results of examination and treatment were analyzed in 397 patients with acute obturation intestinal obstruction and acute destructive pancreatitis, who had the abdominal compartment syndrome from I to IV degree. The authors showed that on-time decompressive laparotomy allowed the decrease of lethality from 25% to 15-17,8%.